Markterfolg und Erfolgsfaktoren von Genossenschaften und anderen Rechtsformen: Ein Vergleich von deutschen Molkereien anhand betriebswirtschaftlicher Kennzahlen; Market Success and Factors of Success of Cooperatives and Investor-Owned Firms: An Interfirm Comparison of German Dairies on the Basis of Key Performance Indicators - Roland Zieseniß (German Journal of Agricultural Economics (GJAE), 2014)
– This paper analyzes the business performance of the German dairy industry based on the annual account data of the years from 2005 to 2007. The empirical work examines key performance indicators for the financial security and for the potential yield of the dairy industry. The interfirm comparison of dairy-cooperatives and investor-owned dairies shows significant differences between the two groups such as cooperatives have a higher performance in cooperatives of financial security and disadvantages in earnings indicators.
Keywords: 330; Milchverarbeitung; Agrargenossenschaft; Produktivität; Kapitalstruktur; Deutschland